2021
DOI: 10.1016/j.scs.2021.103175
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating COVID-19 infection disease transmission in indoor environment using physical barriers

Abstract: During the normalized phase of COVID-19, droplets or aerosol particles produced by infected personnel are considered as the potential source of infection with uncertain exposure risk. As such, in densely populated open spaces, it is necessary to adopt strategies to mitigate the risk of infection disease transmission while providing sufficient ventilation air. An example of such strategies is use of physical barriers. In this study, the impact of barrier heights on the spread of aerosol particles is investigate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(66 citation statements)
references
References 45 publications
(54 reference statements)
1
64
0
1
Order By: Relevance
“…Since January 2022, recurring COVID-19 outbreaks have been occurred in multiple places/regions, with the number of new confirmed cases in January reaching a two-year high. As a result of COVID-19, countries have adopted diverse control strategies to reduce the spread of the epidemic, such as keeping social distance and lockdown ( Ren et al 2021 ; Balest and Stawinoga 2022 ), but various sectors have also been affected to varying degrees as a result. Among them, the education sector has been significantly affected, including significant changes in the way of knowledge transmission and the environment of teaching and learning.…”
Section: Introductionmentioning
confidence: 99%
“…Since January 2022, recurring COVID-19 outbreaks have been occurred in multiple places/regions, with the number of new confirmed cases in January reaching a two-year high. As a result of COVID-19, countries have adopted diverse control strategies to reduce the spread of the epidemic, such as keeping social distance and lockdown ( Ren et al 2021 ; Balest and Stawinoga 2022 ), but various sectors have also been affected to varying degrees as a result. Among them, the education sector has been significantly affected, including significant changes in the way of knowledge transmission and the environment of teaching and learning.…”
Section: Introductionmentioning
confidence: 99%
“…Dose-response model (Eq. (13) ) has been widely applied to assess the infection risk involved with viral aerosol inhalation [ [32] , [33] , [34] ], and was utilized in the present investigation. Where p is the infection probability with certain dose of viral inhalation (−), d represents the inhaled virus dose (RNA copies).…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that long-time exposure to PM 2.5 is significantly detrimental to the human body by inhaling such fine PMs moves into the human lungs ( Wang et al, 2006 , Gemenetzis et al, 2006 , Qian et al, 2008 ). In addition, PM 2.5 has a long life in the air and is swiftly suspended in comparison to liquid droplets ( Figure 4 a, 4 b) which is a significant threat to a doctor`s health for a long time indoor conditions ( Ren et al, 2021 ). The PM 2.5 can be stocked on walls, the floor of hospitals chairs, table equipment's surface materials and quite easily moved by tiny turbulence in the air from normal physical activities such as people moving, and walking ( Liu et al, 2018 , Chatoutsidou et al, 2015 , Hanninen et al, 2005 , Zhang and Cao, 2015 , National Ambient 2022 ).…”
Section: Indoor Pollution Issues During “Living With Covid Phase”mentioning
confidence: 99%
“…Reproduced with permission from ref. ( Ren et al, 2021 ) with license number [5177491160146], Copyright Elsevier 2021. …”
Section: Indoor Pollution Issues During “Living With Covid Phase”mentioning
confidence: 99%